Development of Integrated Learning Model of Islamic Education Subject and Student Self Control - Demina Demina; Z Mawardi Effendi; Azwar Ananda; Darmansyah Darmansyah (Jurnal Aplikasi IPTEK Indonesia, 2018)
This research title is the development of integrated learning model of Islamic education subject (PAI) and student self control. The problem of the research is in the orientation of knowledge, the meaning of learning process is still less optimal which is characterized by the weakness of student character. The result of learning process and student study’s value do not success to internalize inside the student. PAI learning process in Madrasah Ibtidayah the method of Teacher Centered still dominates the school. PAI is presented in partial and it is should be not in holistic and integration. Developing research method with ADDIE consists of analysis, design, development, implementation, and evaluation. Syntax model which is developed by ISLAMIC (Information, Synergy, Learning, Active, reminding Model, and Continue). By the instructional effect hoped that the student intelligent increasing and has strong spiritual religious, self control and well behavior. The nurturant effect from this research was the realization of learning process meaning. This integrated study is hoped that the students are able to link one topic to the other subjects. Characters value inside the material expected to be applied in students’ life later on. The result of analysis development model with Aiken validation book model, teacher book and student book showed that the product was valid. The product of book model practicality. Teacher book and student book resulted practical product. Product effectiveness increased the study result and students self control.